Translating Answers to Open-ended Survey Questions in Cross-cultural Research: A Case Study on the Interplay between Translation, Coding, and Analysis. Issue 3 (August 2015) - Behr, Dorothée
Open-ended probing questions in cross-cultural surveys help uncover equivalence problems in cross-cultural survey research. For languages that a project team does not understand, probe answers need to be translated into a common project language. This article presents a case study on translating open-ended, that is, narrative answers. It describes how the translation can be approached to obtain high-quality translations and how translation, coding of answers, and analysis of codes are all deeply interwoven. While the translation of narrative answers is a small field of application, the article's content is also relevant for those who are increasingly setting up cross-cultural cognitive interviewing or for qualitative researchers in general who pay increased attention to the translation of qualitative research data.